A yeast RNA-binding protein shuttles between the nucleus and the cytoplasm. - Flach, J (1994)
RNA-binding proteins have been suggested to move in association with RNA as it leaves the nucleus. The NPL3 gene of the yeast Saccharomyces cerevisiae encodes in nuclear protein with consensus RNA-binding motifs and similarity to heterogeneous nuclear ribonucleoproteins and members of the S/R protein family. We show that although Npl3 is located in the nucleus, it can shuttle between nuclei in yeast heterokaryons. In contrast, other nucleus-targeted proteins do not leave the nucleus under similar conditions. Mutants missing the RNA-binding motifs or the N terminus are still capable of shuttling in and out of the nucleus. Npl3 mutants missing the C terminus fail to localize to the nucleus. Overproduction of Npl3 in wild-type cells shows cell growth. This toxicity depends on the presence of series of unique repeats in the N terminus and localization to the nucleus. We suggest that the properties of Npl3 are consistent with it being involved in export of RNAs from the nucleus.